Electromyographic evaluation of the rectus femoris muscle during exercises performed on the leg press - Tassi, N. [UNESP]; Guazzelli Filho, J. [UNESP]; Gonçalves, M. [UNESP]; Vitti, M. [UNESP]; Krool, L. B. [UNESP] (My University, 1998)
The rectus femoris was analysed in 10 volunteers during knee flexion and extension with the feet in normal, plantar flexion and dorsal flexion positions. Hewlett-Packard surface electrodes, an electromyographic signal amplifier, a computer equipped with an A/D conversion plaque (Model CAD 10/26), software specially designed to record and analyse the signals, Horizontal Leg Press, and electrogoniometers were used. The rectus femoris muscle showed strong potentials at the beginning of knee extension. In the simultaneous bendings of the knee and hip the activity was strong toward the end of the movement. The rectus femoris showed a similar activity both in the upper and lower platforms. As for foot positions, the rectus femoris showed the smallest potentials with the foot in plantar flexion and the largest ones with the foot in dorsal flexion.
Keywords: adult; controlled study; electromyography; foot; human; human experiment; knee function; leg exercise; leg muscle; male; muscle potential; Adult; Electromyography; Exercise; Humans; Leg; Male; Muscle, Skeletal